Effect of epigallocatechin-3-gallate, major ingredient of green tea, on the pharmacokinetics of rosuvastatin in healthy volunteers - Kim TE; Ha N; Kim Y; Kim H; Lee JW; Jeon JY; Kim MG (Dove Medical Press, 2017)
Tae-Eun Kim,1 Na Ha,2 Yunjeong Kim,2 Hyunsook Kim,1 Jae Wook Lee,3 Ji-Young Jeon,2 Min-Gul Kim2,4 1Department of Clinical Pharmacology, Konkuk University Medical Center, Seoul, 2Center for Clinical Pharmacology, Biomedical Research Institute, Chonbuk National University Hospital, Jeonju, Jeonbuk, 3Nephrology Clinic, National Cancer Center, Goyang, Gyeonggi-do, 4Department of Pharmacology, Chonbuk National University Medical School, Jeonju, Jeonbuk, Republic of Korea Abstract: Previous in vitro studies have demonstrated the inhibitory effect of green tea on drug transporters. Because rosuvastatin, a lipid-lowering drug widely used for the prevention of cardiovascular events, is a substrate for many drug transporters, there is a possibility that there is interaction between green tea and rosuvastatin. The aim of this study was to investigate the effect of green tea on the pharmacokinetics of rosuvastatin in healthy volunteers. An open-label, three-treatment, fixed-sequence study was conducted. On Day 1, 20 mg of rosuvastatin was given to all subjects. After a 3-day washout period, the subjects received 20 mg of rosuvastatin plus 300 mg of epigallocatechin-3-gallate (EGCG), a major ingredient of green tea (Day 4). After a 10-day pretreatment of EGCG up to Day 14, they received rosuvastatin (20 mg) plus EGCG (300 mg) once again (Day 15). Blood samples for the pharmacokinetic assessments were collected up to 8 hours after each dose of rosuvastatin. A total of 13 healthy volunteers were enrolled. Compared with the administration of rosuvastatin alone, the concomitant use at Day 4 significantly reduced the area under the concentration–time curve from time 0 to the last measurable time (AUClast) by 19% (geometric mean ratio 0.81, 90% confidence interval [CI] 0.67–0.97) and the peak plasma concentration (Cmax) by 15% (geometric mean ratio 0.85, 90% CI 0.70–1.04). AUClast or Cmax of rosuvastatin on Day 15 was not significantly different from that on Day 1. This study demonstrated that co-administration of EGCG reduces the systemic exposure of rosuvastatin by 19%, and pretreatment of EGCG can eliminate that effect of co-administration of EGCG. Keywords: rosuvastatin, green tea, EGCG, pharmacokinetics, drug interaction, drug transporter